“Women’s Three Bodies”: An Anthropological Perspectiveon Barriers to Safe Abortion Services in KiberaInformal Settlements, Nairobi, Kenya - W.Onyango- Ouma; Edna N. Bosire (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2019)
Background: Abortion remains a critical determinant of maternal morbidity and mortality in Kenya. Recent studies on induced abortion estimated an annual abortion incidence of 48 abortions per 1,000 women of reproductive age, which is higher than other East African countries. In 2010, the Kenyan Constitution widened the provisions under which women qualified for safe abortions. However, majority of women still seek abortion services from unqualified providers. Using an interpretive, meaning-centered approach, this study aims to explore the barriers to safe abortion services in Kibera informal settlements, Nairobi Kenya.Subjects and Method: This was a cross-sectional study encompassing both qualitative and quantitative research methods. We used different sampling techniques (convenient, purposive and snow ball methods) to recruit our study participants (n=55). Quantitative data was collected using a survey questionnaire and data was analyzed by SPSS version 21. Qualitatively, data was collected using Focus Group Discussions (FGDs), Key Informant interviews and case study narratives. This involved note taking and audio recordings, which were transcribed verbatim and thematically analyzed using QSR Nvivo 21 software.Results: This study revealed that women